Delay Identification of the HVAC Project on West Madura Offshore Oil Company Using the House of Risk Method - Gunawan Kunto Bhasworo; Ervina Ahyudanari (Institut Teknologi Sepuluh Nopember, 2020)
This research is focused on the analysis of delays or risks to the implementation of the